Efekt neinvazivní stimulace mozku na hypokinetickou dysartrii, mikrografii a mozkovou plasticitu u pacientů s Parkinsonovou nemocí - Mekyska, Jiří; Rektorová, Irena (2020)
Hypokinetic dysarthria (HD) is common in Parkinson’s disease (PD) patients and it responds only partially to pharmacotherapy and surgery of PD. We will explore short-term effects of repetitive transcranial magnetic stimulation (rTMS) applied over pre-defined brain regions using both high and low frequency TMS protocols on HD and micrographia in PD, and on related brain plasticity changes. To achieve our goal we will combine acoustic analysis and functional MRI with rTMS. The objective is to identify an optimal rTMS protocol and stimulation site to improve HD and micrographia in PD patients on dopaminergic medication. Based on these results a repeated-sessions rTMS study will be designed to investigate long-term effects of rTMS on HD in PD and related changes in brain structure and function. The project results will allow for the identification of potential therapeutic effects of rTMS as a tool that could contribute to the speech therapy of HD in PD patients. The results will also enhance our understanding of brain mechanisms underlying specific long-term effects of rTMS.
Závěrečná zpráva o řešení grantu Agentury pro zdravotnický výzkum MZ ČR
Keywords: klinické protokoly; Humans; Parkinsonova nemoc; lidé; magnetická rezonanční tomografie; dysartrie; Treatment Outcome; Magnetic Resonance Imaging; neurologie; Neuronal Plasticity; Pilot Projects; pilotní projekty; Transcranial Magnetic Stimulation; výsledek terapie; Dysarthria; Clinical Protocols; Parkinson Disease; Acoustics; neuroplasticita; akustika; transkraniální magnetická stimulace